Managing Emotions and Motivation: Psychological Strategies in Volleyball Learning - Ferdiyanto, Yogi; Yulisatria, Guntur; Suhariyanti , Mela (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The purpose of this study was to examine the intervention of mindfulness training in emotion management and motivation in improving students' engagement and achievement in learning volleyball at Vocational High School. This research is experimental research. The quasi-experimental method used is one group pretest-posttest design. Mindfulness intervention is implemented directly with participants by carrying out mindfulness meditation as an effort to manage students' emotions and motivation. for motivation using a sports achievement motivation instrument adapted by Miftah Janah based on Smith's theory. The results of this study show that mindfulness training intervention has a significant effect in improving emotional intelligence and student motivation in learning volleyball at SMK Muhammadiyah Abung Semuli. The conclusion of the research is that mindfulness training can increase students' emotional intelligence and motivation in learning volleyball. Thus, providing treatment in the form of mindfulness exercises has a positive impact on students, namely increasing the level of emotional intelligence and student motivation in learning volleyball.